MENUMBUHKAN KECINTAAN TERHADAP AL-QUR’AN MELALUI PESANTREN KILAT DI RUMAH TAHFIDZ NURUL ILMI 316 - Heriyani, Endang (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
During school holidays, parents worry about the activities chosen by their children. The activity that children like the most is playing gadgets during holidays. This can have a negative impact on children. Pesantren kilat is an alternative activity that can be chosen by children to fill school holidays. This community service aims to foster children's love for the Qur'an through flash pesantren activities. The methods of devotion include observation, service implementation, and evaluation. The conclusion obtained from the implementation of the pesantren kilat is that some students began to grow their love for the Qur'an. Santri looked serious and enthusiastic when given lessons in the Qur'an and when memorizing the Qur'an. Furthermore, followed up by registering as mukim students at Rumah Tahfidz Nurul Ilmi 316 as many as 1 person, and 6 people as non-mukim students to learn and memorize the Qur'an.